A case of paroxysmal complete atrioventricular block in a COVID‐19 patient - Hong Nyun Kim (Wiley, 2021)
Abstract Many types of cardiac arrhythmias can occur in people with COVID‐19, and these arrhythmias can affect the patient's outcomes. We have experienced paroxysmal complete atrioventricular block in a patient with COVID‐19 and would like to share the course of treatment.